Integrating Advanced Digital Technologies in Event Tourism: Reframing “Quantum Tourism” within Smart Destination Development in Bali - Ni Made Eka Mahadewi; Dahlan Abdullah (Centre of Excellence in Tourism Udayana University, 2026)
The acceleration of digital transformation in tourism has intensified the need for destinations to adopt advanced technologies to enhance competitiveness and visitor experience. While emerging narratives such as “quantum tourism” have gained attention, the concept remains theoretically ambiguous and empirically underexplored. This study aims to critically examine the role of advanced digital technologies in Bali’s event tourism ecosystem and to reassess the conceptual validity of “quantum tourism” within a smart destination framework. A qualitative-dominant mixed-method approach was employed, combining questionnaire data (n = 101) with semi-structured interviews and field observations involving key tourism stakeholders. The findings indicate that while digital technologies—particularly mobile platforms and Internet of Things (IoT)—are widely adopted (92.1%), stakeholders demonstrate limited understanding of advanced technological paradigms labeled as “quantum.” This study reframes “quantum tourism” as a metaphorical construct reflecting complexity, interconnectivity, and adaptive systems rather than a distinct technological domain. Managerial implications emphasize the need for realistic digital strategies, capacity building, and evidence-based technology adoption.